THE IDENTIFICATION OF MANGO MORPHOLOGY AND ANATOMY (MANGIFERAINDICA L) AT WEST TOBOLI AND POMBALOWO VILLAGE, PARIGI MOUTONG. - Widya Tri Wulandari; Nirwan Sahiri; Enny Adelina (Tadulako University, 2018)
Mango (Mangiferaindica L.) is a type of tropical fruit which is favored by people in the world and becomes a commodity trade between countries. According to the information, known as mango The Best Loved-Tropical, accompany the popularity of durian as the King of Fruit. The main product of the mango is its thatis usuallyconsumed in fresh or processed products. But in addition to the fruit,,other components that also played an important role were the mangoes leaves than can be benefit from medicinal plants as an alternative. This research aimed to obtain a diversity of mango tree based on morphological and anatomical analysis of plant the mango in the West Toboli village and Pombalowo Regency, Parigi Moutong Regency. This research was carried out in the village of West Toboli, District Toboli Parigi North and the village of Pombalowo sub-district of Parigi, Parigiranga Reddy District and Laboratory Science (FMIPA), the University of Tadulako conducted in July to August 2016. This research method using exploratory, as for a character that observed was the height of the plant (m), diameter (cm), the shape of the canopy, the long strands of leaves (cm) width (cm) leaf blade, petiole length (cm). Cluster analysis results in the village there were three groups of Western Toboli diverse namely TBB12, TBB14 and TBB11, in the village of Pombalowo there were three diverse groups namely PBL1, PBL5 and PBL8. Whereas in the second the village obtained a combined five diverse groups namely TBB12, TBB14, TBB2, PBL1 and TBB11. Characters that distinguished the selected accessions were the height of plants, and the diameter of the rod.